Persepsi Harga dan Lokasi Terhadap Keputusan Pembelian Berbahan Baku Sayur Olahan - Masitah, Tina Herianty; Sriangraini, Puri; Hakim, Mukti (JURNAL AGROPLASMA, 2025)
This type of research utilizes quantitative research and collects data through interviews, observations, and questionnaires. The independent variables of this study include taste, price perception, and location, while the dependent variable in this study is the purchasing decision. The sample consists of 50 individuals who purchased processed vegetable ingredients (Pecal) Bik Sungam, who have previously bought processed vegetable ingredients, namely processed vegetable ingredients (Pecal) Bik Sungam. The sampling technique used is simple random sampling, or a method of sampling randomly from the population without considering the existing strata. The data analysis conducted includes multiple linear regression analysis, hypothesis testing with t-tests, and f-tests. The results of this study indicate that the taste variable (X1) has no effect on the purchasing decision (Y) with a calculated t value of (1.833) < t table (2.014) and a significance value of (0.073) > 0.0.5, The price perception variable (X2) affects the purchasing decision (Y) with a calculated t value of (2.118) < t table (2.014) and a significance value of (0.040) < 0.05. The location variable (X3) affects the purchasing decision (Y) with a calculated t value of (3.077) > t table (2.014) and a significance value of (0.004) < 0.05. The results of the study simultaneously obtained an F value of 8.322 > F table 2.80 and a significance value of 0.000 < 0.05, indicating that taste (X1), price perception (X2), and location (X3) simultaneously have a significant effect on the purchasing decision (Y) of processed vegetable-based ingredients (Pecal) Bik Sungam.  Keywords: taste, price perception, location, purchasing decision